FIGURE 2 in Redescription and neotype designation of the Antarctic springtail Folsomotoma octooculata (Collembola: Isotomidae) - Fanciulli, Pietro Paolo; Leo, Chiara; Convey, Peter; Frati, Francesco; Carapelli, Antonio (Zenodo, 2018)
FIGURE 2. Folsomotoma octooculata; A, Number and distribution of dorsal sensilla (accp–s, al–s and as) and microsensilla (ms); B, C, E, F, Number and distribution of dorsal aXial setae along Th. II (E), Th. III (F), Abd. I (B) and Abd. II (C); asterisks indicate setae alWays present in all the specimens obserVed; D, ChaetotaXy of Abd. V–VI; G, Abd. IV p roW shoWing the position of the accp–s. Scale bar: 50 µm (D, G). : Published as part of Fanciulli, Pietro Paolo, Leo, Chiara, Convey, Peter, Frati, Francesco & Carapelli, Antonio, 2018, Redescription and neotype designation of the Antarctic springtail Folsomotoma octooculata (Collembola: Isotomidae), pp. 392-400 in Zootaxa 4392 (2) on page 396, DOI: 10.11646/zootaxa.4392.2.11, http://zenodo.org/record/1195334